Impact of doping on the performance of p-type Be-doped Al0.29 Ga0.71As Schottky diodes - Henini, M. (Elsevier, 2017)
The effects of changing the acceptors concentration on the electrical characteristics of Au/Ti on Be-doped Al0.29Ga0.71As Schottky contact have been investigated in the temperature range of 100–400 K. Using three devices with three different doping levels, the barrier height (ΦB), ideality factor (n) and series resistance (RS) for each diode were evaluated using both thermionic emission (TE) theory and Cheung's method. Our experimental results showed that the sample with a moderate doping concentration of 3×1016 cm-3 has the best performance, including ideality factor of 1.25 and rectification ratio of 2.24×103 at room temperature. All samples showed an abnormal behavior of reducing ΦB and increasing n with increase of temperature. This behavior was attributed, in case of low concertation samples, to barrier inhomogeneity and was explained by assuming a Gaussian distribution of barrier heights at the interface. While for the heavily doped sample, such non-ideal manner was ascribed with tunneling through the field emission (FE) mechanism.